The Influence of Physical Work Environment and Work Discipline on The Performance of Celikah Health Center Employees - Monica Sapitri; Meilin Veronica; Muhammad Bahrul Ulum (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2023)
This study aims to determine how the influence of the physical work environment and work discipline partially and simultaneously on employee performance at the Celikah Health Center, Kayuagung District, OKI Regency. In this study collected through distributing questionnaires with 80 respondents. The data analysis technique used is multiple linear regression analysis models, with t tests and F tests. While what is used to see the extent of the accuracy and feasibility of the research instrument (measuring variables) is used validity and reliability tests. The results of this study indicate that partially the physical work environment has a significant effect and work discipline has a significant effect on employee performance at the Celikah Health Center, Kayuagung District, OKI Regency. The results of the F test analysis and the coefficient of determination show that simultaneously the physical work environment and work discipline have a positive and significant influence on employee performance at the Celikah Health Center, Kayuagung District, OKI Regency. This shows that the better the physical work environment and the higher the work discipline that exists in employees, the better and higher the performance produced by employees of the Celikah Health Center, Kayuagung District, OKI Regency.